Early Cretaceous parasitism in amber: A new species of Burmazelmira fly (Diptera: Archizelmiridae) parasitized by a Leptus sp. mite (Acari, Erythraeidae). (June 2018) - Arillo, Antonio; Blagoderov, Vladimir; Peñalver, Enrique
Abstract: A new species of the extinct family Archizelmiridae, Burmazelmira grimaldii n. sp. (Diptera: Sciaroidea), is described from the Spanish Lower Cretaceous (upper Albian) amber of San Just outcrop in the Maestrazgo Basin (Province of Teruel) based on two complete specimens. A comparison with the only previously known species of the genus, Burmazelmira aristica Grimaldi, Amorim and Blagoderov, 2003, is provided. The new species is diagnosed based on antennal features. One of the flies is parasitized by a larval Leptus sp. mite (Acari, Erythraeidae). Despite the abundance of Leptus mites in several localities of Spanish amber, it is only the third record of a Leptus attached to a host. Records of parasitism are very rare in Cretaceous ambers, unlike in Cenozoic ones. A list of the known records of dipterans parasitized by mites in amber, virtually the only medium that can preserve this relationship in the fossil record, is provided.